2000
DOI: 10.1111/1468-036x.00126
|View full text |Cite
|
Sign up to set email alerts
|

A survey into the use of derivatives by large non‐financial firms operating in Belgium

Abstract: Empirical evidence on the use of derivatives for risk management on the European continent is virtually non-existent. To fill this gap, our survey documents the usage of derivatives by non-financial large firms operating in Belgium. This paper provides descriptive evidence with respect to several questions that are raised in the literature. Why do firms hedge? Which financial risks are being managed? How widespread is the use of derivatives? Which derivatives are used for which purposes? How is a risk manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 9 publications
1
44
0
Order By: Relevance
“…In a follow-up survey seven years later, it was found that the rate of derivative use had increased to 59% of firms (Alkeback, Hagelin and Pamborg, 2006). In a survey of derivative use by large Belgian firms, De Ceuster, Durinck, Laveren and Lodewyckx (2000) found that 66% of firms use derivatives. In the Netherlands, it was found that 60% of Dutch firms use derivatives (Bodnar, de Jong and Macrae, 2003).…”
Section: Review Of Prior Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…In a follow-up survey seven years later, it was found that the rate of derivative use had increased to 59% of firms (Alkeback, Hagelin and Pamborg, 2006). In a survey of derivative use by large Belgian firms, De Ceuster, Durinck, Laveren and Lodewyckx (2000) found that 66% of firms use derivatives. In the Netherlands, it was found that 60% of Dutch firms use derivatives (Bodnar, de Jong and Macrae, 2003).…”
Section: Review Of Prior Surveysmentioning
confidence: 99%
“…Belgian firms mainly hedge currency risk, both current contractual obligations and anticipated transactions up to one year as well as interest rate risk. Only 16% of firms hedge commodity risk (De Ceuster, Durinck, Laveren and Lodewyckx, 2000).…”
Section: E the Reasons Companies Use Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of recent survey studies, additional countries have been studied, such as New Zealand (Berkman, Bradbury and Magan, 1997), Sweden (Alkebäck and Hagelin, 1999), Germany (Gebhardt and Russ, 1999), Belgium (De Ceuster, Durinck, Laveren and Lodewyckx, 2000), UK (Mallin, Ow-Yong and Reynolds, 2001) and Switzerland (Loderer and Pichler, 2000). This paper investigates derivative use in risk management of firms in the Netherlands and compares it with the established evidence from firms in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this, the empirical results of study by Chang [19] pointed out how hedging will play an effective role in helping corporations to manage adverse outcomes of exchange rate risks. The surveys of the past study such as Bodnar and Gebhardt [20]; Bodnar et al [21]; Prevost et al [22]; De Ceuster et al [23] suggests that, firms actively manage FX risk using internal and external (derivatives) instruments. Then again, there are no real long term derivatives available (except currency swaps) to hedge the economic exposure.…”
Section: Literature Reviewmentioning
confidence: 99%